HAPLOIDENTICAL STEM CELL TRANSPLANTATION - Fatobene, Giancarlo; Kerbauy, Mariana Nassif; Hamerschlak, Nelson; Rocha, Vanderson (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION